Kirenol alleviates diabetic nephropathy via regulating TGF-β/Smads and the NF-κB signal pathway - Jialin Li; Jiawen Zhang; Meng Yang; Xiaocui Huang; Meng Zhang; Xiansong Fang; Suzhen Wu (Taylor & Francis Group, 2022)
Context Kirenol possesses anti-inflammatory, antifibrotic and anti-arthritic effects. However, its reno-protective effects against diabetic nephropathy (DN) have not been evaluated.Objective This study explores the reno-protective effects of kirenol against DN and clarifies the potential mechanisms.Materials and methods The mesangial cells were treated with 20 µM kirenol and 10 ng/mL human recombinant TGF-β1 or 30 mM glucose for 24 h. Then the cells were harvested to assay the expression of the target genes or proteins. Thirty C57BL/6J male mice were given high-fat diet with streptozotocin injection to induce diabetes and then were randomized into three groups (n = 10): vehicle administration (DM group), 2 mg/kg kirenol (DM + kirenol group) and 200 mg/kg metformin (Met group) for 3 months, orally. A healthy group (Con, n = 10) was included as the control.Results Compared to the DM group, kirenol treatment decreased the phosphorylation of Smad2/3 and NF-κB (0.64- and 0.43-fold) as well as the accumulation of FN and Col IV (0.58- and 0.35-fold); moreover, the expression of IκBα was restored to normal level by kirenol treatment both in vivo and in vitro. After kirenol treatment, IL-6 expression was decreased 0.35- and 0.57-fold, and TNF-α expression was decreased 0.34- and 0.46-fold, in vitro and in vivo, respectively. Furthermore, kirenol alleviated the glomerular basement membrane thickness and foot process fusion.Discussion and conclusions Kirenol could alleviate DN by downregulating the TGF-β/Smads and the NF-κB signal pathway. Our study provides a potential mechanism for the treatment of DN with kirenol.